Measuring technical efficiency of insurance companies using dynamic network DEA: an intermediation approach - Nourani, Mohammad; Devadason, Evelyn Shyamala; Chandran, VGR (Technological and Economic Development of Economy, 2018)
This study measures technical efficiency of the Malaysian insurance companies using a new framework for performance efficiency, built on the intermediation approach, by decomposing the complex service processes of insurance companies into two functional divisions, premium accumulation and investment capability. The study employs a dynamic network data envelopment analysis for performance evaluation of insurer (life, general and composite insurers) and ownership (local and foreign) types, spanning the period 2007–2014. The findings reveal a lack of efficiency in the investment capability function among local insurers as compared to their foreign counterparts. While the composite or non-specialized segment performs better in the investment capability function, the general segment achieves better efficiency in the premium accumulation function. The results suggest the high usage of input quantities and lack of total investment as key reasons for low efficiency, particularly among the local insurers. Implications for business excellence for insurance companies are further discussed.